Factors that influence individual’s intention to participate in family takaful scheme among community in Taman Permint, Dungun / Nur Atiqah Abdul Salam - Abdul Salam, Nur Atiqah (2024)
This paper aimed to identify the Factors that Influence Individual’s Intention to Participate in Family Takaful Scheme among community in Taman Permint, Dungun. This study begins with the brief about Family Takaful Scheme. A set of questionnaires was distributed to the respondent among community in Taman Permint, Dungun using probability sampling and 100 questionnaires have been returned. The data analysed using Descriptive Analysis and Reliability by using Statistical Package for Social Science (SPSS). Finally, the limitation and recommendation are included to help further research to have a better finding of the result.